Garnet morphology distribution in the northern part of the Moine Supergroup, Scottish Caledonides. (2nd October 2016) - Ashley, K. T.; Law, R. D.; Thigpen, J. R.
Abstract: Garnet is a versatile and useful indicator mineral exploited in numerous geological studies. Despite its utility in providing thermobarometry and geochronology constraints, many difficulties remain in making meaningful interpretations of such data. In this paper, we characterize garnet grains from over 140 garnet‐bearing metasedimentary rock samples collected from the northern part of the Moine Supergroup (Scottish Caledonides). Large, euhedral garnet grains are interpreted to be indicative of prograde metamorphic growth during the most recent (Scandian, c . 430 Ma) phase of orogenesis. Anhedral garnet is largely restricted to the relatively low‐grade (greenschist – lower amphibolite facies) Moine thrust sheet, with an abrupt change in morphology and grain size when traced across the overlying Ben Hope and Sgurr Beag thrusts into the higher grade, more hinterland‐positioned thrust sheets. Our results suggest that caution should be exercised in using anhedral garnet in the Moine thrust sheet to estimate peak P–T conditions associated with low temperature (< 500 °C) Scandian metamorphism, because in at least some cases garnet growth may have occurred during an earlier metamorphic event. However, chemical and isotopic data from this structurally lower anhedral garnet may still be useful for deconvolving a possible polymetamorphic history for this thrust sheet. In the immediately overlying Ben Hope thrust sheet, garnet has prograde euhedral (Scandian?) rims, indicating that the Ben Hope thrust must represent a significant thermal and/or chemical break. Inclusion distribution and mineral assemblages in garnet have been used to gain further insight on garnet growth conditions and to distinguish garnet that likely contains multiple generations of growth. Although our results are specific to the Caledonides of northern Scotland, this work highlights the general necessity of a comprehensive petrographic assessment in advance of interpreting large suites of garnet‐derived thermodynamic and geochronological data.